Testing for HIV – the first three decades. (April 2015) - Busch, M. P.
<x xml:space="preserve">Abstract</x> Background HIV was discovered in 1984, with high rates of virus isolation and antibody (Ab) detection in haemophiliacs and recipients of blood from HIV‐infected donors, demonstrating the critical need to develop tests for donor screening. Aims/Methods Review evolution of HIV‐donor screening, and broader applications of HIV tests and infected‐donor surveillance to research and public health. Results In mid‐1984, scientists in governments and industry collaborated to develop HIV‐Ab tests that were implemented in blood banks ~1 year following discovery of HIV. Initial Ab screening did not eliminate TT‐HIV, however, with numerous breakthrough cases detected following introduction of first‐generation assays, which were determined to have an infectious pre‐seroconversion (SC) window period (WP) of ~56 days. Improvements in sensitivity of second‐generation tests in the late‐1980s and third‐generation tests in the mid‐1990s reduced the pre‐SC WP to approximately 3 weeks. Subsequent additions of p24 antigen and then nucleic acid technology (NAT)‐screening in the late 1990s closed the infectious WP to 5–10 days. NAT‐screening assays and algorithms and fourth‐generation Ag/Ab serological tests developed for blood bank screening and staging of early HIV infections are now in widespread use in clinical diagnostic, research and public health settings. NAT assays developed for donor screening have been applied to detect persistent low‐level viral replication in studies of patients on HAART, 'elite controllers' and 'HIV‐eradication' research. Conclusions Progressive improvements in HIV screening assays have virtually eliminated TT‐HIV infections, and consequent advances in HIV testing have contributed to HIV diagnostics, research and public health.